Reevaluating the -20° Astronomical Dawn Angle: An Islamic Jurisprudential and Astronomical Analysis of Subh Time Determination in South Sulawesi - Wahidin; Abd. Karim Faiz; Muh. Rasywan Syarif (Faculty of Law, Universitas Pekalongan, 2025)
The -20o dawn standard that applies in Indonesia has become a problem when the results of observations and research show that the appearance of dawn with the -20o standard is considered too fast. Based on this, researchers in this study conducted dawn observations in South Sulawesi at Aparalang Cliff in Bulukumba. The purpose of this study is to describe the method and basis of the Ministry of Religious Affairs of the Republic of Indonesia regarding the determination of dawn -20o. Second, to analyse the data of dawn appearance in Aparalang Cliff, Bulukumba, South Sulawesi based on digital image instrument. Third, to analyse the variation of dawn data from the perspective of wadh'i law. This research method is qualitative with observation at Aparalang Cliff with location specifications -5o 32' 14